PENGARUH KUALITAS PRODUK, ORIENTASI PASAR DAN PENJUALAN ADAPTIF TERHADAP KINERJA PEMASARAN MELALUI KEUNGGULAN BERSAING PADA MITRA USAHA PT. NATURAL NUSANTARA DI KECAMATAN PRIGEN PASURUAN - Emil, Kamila; Sari, Dewi Komala (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the effect of product quality, market orientation and adaptive sales on marketing performance and competitive advantage in business partners of pt. natural archipelago in prigen district, pasuruan. this study uses a quantitative approach. sampling in this study using simple random sampling technique, with a population of 250 respondents and the sample used amounted to 71 respondents. samples were taken using the simple random sampling method. the data analysis technique used is pls-sem analysis with the smartpls 3.0 program. Keywords: Product Quality, Market Orientation, Adaptive Sales, Marketing Performance, Competitive Advantage